(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2017)
There is little attention in the Baltics dedicated to the research of ports as economic subjects and their impact on environment. It is vital to strengthen the links between the ports and the Blue Growth while raising awareness of the Blue Growth and making it a cross-cutting issue of the sea-oriented priority areas by creating a special mechanism to support Blue Growth which so far has had insignificant links to port operations. The aim of the article is to analyze the trends and summarize the measures already taken for promotion and integration of the Blue Growth in the Baltic Sea region, and to develop guidelines for ports based on the general and the Baltic Sea Blue Growth strategy, to draw conclusions and to submit proposals for improvement and increase of the Blue Growth. Latvia needs to develop an action plan in order, without unnecessary errors, to quickly implement sustainable port infrastructure and reduce pollution of the sea. The task is to identify the best practices for usage of marine/coastal resources for economic development, and for identification and testing of new smart specialization measures.